2015
DOI: 10.1007/s10508-014-0451-7
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to Sexual Victimization in Female and Male College Students in Brazil: Cross-Sectional and Prospective Evidence

Abstract: Using both cross-sectional and prospective analyses, this study examined vulnerability factors for sexual victimization in 541 female and male Brazilian college students, of whom a subgroup of 250 took part in two measurements 6 months apart. Risk factors for sexual victimization (alcohol consumption, casual sex, and ambiguous communication) in participants' cognitive scripts for consensual sex were linked to sexual victimization via their translation into risky sexual behavior. Pornography use was indirectly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 63 publications
4
31
1
6
Order By: Relevance
“…Third, many studies were unable to differentiate between sexual abuse (before age 14) and sexual aggression in adulthood (after age 14). Although childhood sexual abuse may act as a risk factor for later sexual victimization 49 , the two phenomena relate to distinct underlying mechanisms. Fourth, in addition to the lack of information on time frame, location, and sample age, some studies failed to provide clear information on how they defined sexual aggression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, many studies were unable to differentiate between sexual abuse (before age 14) and sexual aggression in adulthood (after age 14). Although childhood sexual abuse may act as a risk factor for later sexual victimization 49 , the two phenomena relate to distinct underlying mechanisms. Fourth, in addition to the lack of information on time frame, location, and sample age, some studies failed to provide clear information on how they defined sexual aggression.…”
Section: Discussionmentioning
confidence: 99%
“…To address those gaps and better orient public policies, I outline some suggestions for future research in Brazil: (1) self-report studies on sexual aggression and victimization with representative samples of the Brazilian population, identifying the differences across the five major geographic regions; (2) studies that address sexual aggression from a developmental and longitudinal perspective, from young age until late adulthood, seeking to understand the onset, severity, and persistence of the problem over the years; few Brazilian studies have addressed sexual victimization and perpetration prospectively 49,51 ; (3) studies that differentiate between childhood sexual abuse and sexual aggression i.e., sexual victimization before and after age 14, respectively; (4) studies that address sexual aggression and victimization in both men and women, taking sexual orientation and skin color into consideration; (5) studies that address incidence of sexual aggression in the previous year, using a behaviorally specific description of the legal definition of rape in Brazil, such as proposed by SES 16 , so that rates can be directly compared to the official data on rape in Brazil; (6) studies that confirm if, and explain why, specific social groups (e.g., homosexuals and bisexuals, and university students) may have higher vulnerability for sexual victimization and perpetration.…”
Section: Discussionmentioning
confidence: 99%
“…24 Showing the family's routine in the virtual environment proved to be a risky environment for sexual violence, leaving young people in vulnerable situations by using the internet as a strategy for self-affirmation. [25][26] It is noticeable the importance of parents in maintaining a healthy and close relationship with their children, including education and supervision in the use of social networks and exposure of images that may compromise the lives of these adolescents.…”
Section: /13mentioning
confidence: 99%
“…These sexual behaviors, however, seem to increase the risk of sexual victimization. Various scholars have shown that having a greater number of sexual partners and earlier initiation of sexual activity is associated with experiencing sexual assault (D'Abreu & Krahe, 2016;Hartwick et al, 2007;Schraiber et al, 2008). These studies found that both sexual behaviors increase the risk for women, but only the number of sexual partners increased the risk for men.…”
Section: Risk Factorsmentioning
confidence: 99%